Transcriptome analysis of male and female Sebastiscus marmoratus. - Lingbin Sun (Public Library of Science (PLoS), 2012)
Background The rockfish Sebastiscus marmoratus, which is widely distributed in the East Sea and the South Sea of China, is a sensitive model for the toxic effects and mechanisms of marine contaminants. To gain a global view of the molecular mechanism(s) whereby gene expression may influence sexual dimorphism in S. marmoratus, and to develop a database for further toxicological studies, we performed a large-scale transcriptome study. Methodology/principal findings The Illumina DNA sequencing platform was employed to obtain 27,559,578 and 25,821,126 reads from two cDNA libraries generated from adult male and female S. marmoratus, respectively. Transcriptome de novo assembly was carried out with the short reads assembling program-SOAPdenovo. The reads assembled into 78,675 unigenes, of which 38,677 showed homology to existing protein sequences. Clusters of orthologous groups, gene orthology, and the Kyoto Encyclopedia of Genes and Genomes annotations were performed to better understand the functions of these unigenes. There were 1,209 potential sex differentially expressed unigenes, with 1,049 predicted to be differentially expressed in females and 160 in males. Fifteen randomly chosen unigenes were confirmed using real-time PCR as female or male predominantly expressed genes. Conclusions/significance This is the first report of an annotated transcriptome of S. marmoratus and identification of sex differentially expressed genes. These data will be of interest to researchers using this model. This work also provides an archive for future studies in molecular mechanisms of sexual dimorphism and evolution and can be used in comparative studies of other fish.